1970
DOI: 10.1021/jf60172a026
|View full text |Cite
|
Sign up to set email alerts
|

Flavor and flatulence factors in soybean protein products

Abstract: Extracting 99.8% of the oil from full-fat soybean flakes with pentane-hexane removed little, if any, of the beany, bitter, green flavors. Further extraction of defatted flakes with aqueous ethanol solutions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(36 citation statements)
references
References 16 publications
0
34
0
2
Order By: Relevance
“…Of those 14 components identified in CSPI, the following seven compounds, hexanal, ethyl acetate, pentanal, 2-pentyl furan, ethyl caprylate, 2-heptanone, and 1-octen-3-ol were the main volatiles from the point of view of their content; all of them having been reported as the lipoxygenase catalyzed oxidation products of polyunsaturated fatty acids (MacLeod & Ames, 1988;Rackis, Honig, Sessa, & Steggerda, 1970;Sessa, 1979;Wolf, 1975). The other seven compounds, 3-octen-2-one, ethyl decylate, 1-hexanol, benzaldehyde, cyclohexanone, 1-pentanol, 1-decanol and other minor components were also reported to be present in soy extract.…”
Section: Off-flavor Volatiles In Soy Protein Isolatesmentioning
confidence: 99%
“…Of those 14 components identified in CSPI, the following seven compounds, hexanal, ethyl acetate, pentanal, 2-pentyl furan, ethyl caprylate, 2-heptanone, and 1-octen-3-ol were the main volatiles from the point of view of their content; all of them having been reported as the lipoxygenase catalyzed oxidation products of polyunsaturated fatty acids (MacLeod & Ames, 1988;Rackis, Honig, Sessa, & Steggerda, 1970;Sessa, 1979;Wolf, 1975). The other seven compounds, 3-octen-2-one, ethyl decylate, 1-hexanol, benzaldehyde, cyclohexanone, 1-pentanol, 1-decanol and other minor components were also reported to be present in soy extract.…”
Section: Off-flavor Volatiles In Soy Protein Isolatesmentioning
confidence: 99%
“…On the other hand, some phenolic acids may have flatulence inhibiting properties. Rackis et al (1970) reported that phenolic acids such as syringic and ferulic inhibited flatulence from soybean meals in both in-vitro and in-vivo studies.…”
Section: Nutritional Effectsmentioning
confidence: 99%
“…Their primary role is thought to be reserve carbohydrates for short-and long-term purposes and for transport (Chatterton et al, 1990, Dini et al, 1989, Pharr and Sox, 1984, and protection of plants against cold and seeds against desiccation (Kandler and Hopf, 1980;Saravitz et al, 1987). Nevertheless, the RO have been implicated as causative factors for flatulence after ingestion of food containing soybean meals (Rackis et al, 1970).…”
Section: Introductionmentioning
confidence: 99%